Local referrals as a strategy for increasing value of surgical care among medicare patients undergoing liver and pancreatic surgery. Issue 11 (November 2019) - Merath, Katiuscha; Chen, Qinyu; Diaz, Adrian; Johnson, Morgan; Mehta, Rittal; Dillhoff, Mary; Cloyd, Jordan; Pawlik, Timothy M.
Abstract: Background: The focus of the current Medicare payment reform is to increase value – i.e. improve health care quality while lowering costs. This study sought to define cost variation and surgical quality among hospitals within small geographic areas typical of work commute patterns. Methods: Medicare Provider Analysis and Review (MEDPAR) Inpatient Files was used to identify patients undergoing elective liver and pancreatic surgery between 2013 and 2015. Hospitals were assigned to combined statistical areas (CSAs) based on zip codes. Average price-standardized Medicare payments were used to identify highest- and lowest-cost hospitals within CSAs, and clinical outcomes were compared. Results: The study included 12, 016 patients. Medicare payments for index hospitalization were 45% (12, 580), 42% (16, 831), 44% (12, 901) and 50% (18, 605) higher for the highest-vs. lowest-cost hospitals for non-complex pancreatic procedures, complex pancreatic procedures, non-complex liver procedures, and complex liver procedures, respectively. Surgical quality was worse at highest-vs. lowest-cost hospitals, demonstrated by higher rates of complications, prolonged LOS and 90-day mortality. Conclusion: There was a significant variation in surgical cost for each procedure between CSAs, and within CSAs. Highest-cost hospitals demonstrated worse quality metrics than the lowest-cost hospitals. Local referrals to low-cost hospitals represent an opportunity for increasing value of surgical care.